Making markets in the welfare state the politics of varying market reforms - Gingrich, Jane R., 1978- (Cambridge studies in comparative politics., 2011)
"In 1980, Ronald Reagan was elected President of the United States on the promise of radically reforming American government by cutting spending and welfare entitlements and improving conditions for private entrepreneurship. For Reagan, American government was akin to an alligator infested swamp, not only stagnant but dangerous. Thousands of miles away, the Swedish Prime Minister, Olof Palme, in response to a local government's attempt to privatize a childcare center, took a different stance. Palme argued that the introduction of markets would create "Kentucky Fried Children," the market standing for things American and unhealthy, a threat to Swedish children and the Swedish welfare state"--